ANALISIS PEMBAGIAN HARTA BERSAMA DALAM KONDISI MATI KALALAH (Studi Kasus Putusan Nomor 197K/AG/2015) - Tetty Hariyati; Wahyuni Retnowulandari (Jurnal Hukum Adigama, 2018)
The division of community property is a very essential issue in domestic life. Regarding the positive law taking in force in Indonesia, the division of community property for Islam is regulated in the Compilation of Islamic Law (KHI) where the Compilation of Islamic Law regulates the division of community property for both widowed (widowed and not remarried) and divorced (divorced and not remarried). The widowed is regulated in article 96 of the Compilation of Islamic Law and the divorced is regulated in article 97 of the Compilation of Islamic Law. If examined from these two articles, both equally regulates  if the marriage relationship broke up, the community property is divided for husband and wife, each will get a 50:50 part. However, this is different based upon  Decision Number 197K / AG / 2015 The division is greater for the wife of 60% and 40% for husband. In this case the problem raised here is how the regulation makes an arrangement for division of community property in dead condition without father and children (mati kalalah) under the law of inheritance in Indonesia and how the judge's consideration related to the division of community property in dead condition without father and children (case study: Decision number 197K / AG / 2015)? The author here used normative legal research method that is descriptive and primary and secondary data and also supported by interviews in this study.